Investigation for Cryptosporidiosis in some species of wild and domestic birds and study of histopathological changes which combined of it. - Ikhlas A. Marhoon; Ghydaa A. Jasim (Al-Qadisiyah Journal of Pure Science, 2018)
The present study aimed to investigate of Cryptosporidiosis in some wild and domestic birds, and study the histopathological changes which parasite produced it . To attainment this purpose : A total of 236 birds were collected from different regions of Al-Diwaniya province between May 2013 to June 2014 , Birds included six species which are : Turkey( Meleagris gallopova) ,Quail (Coturnix coturnix ), Domestic chicken (Gallus gallus domesticus) ,Caged chicken(Gallus gallus) ,Commen duck (Anas platyrhynchos) and Feral pigeon (Columba livia). Fecal samples were examined by used hot modified Zeihl-Nelseen stain.   Results revealed that the birds were infected with Intestinal Cryptosporidiosis (58.1%).The study recorded four species belong to Cryptosporidium be responsible for infection : C.parvum ,C.meleagridis , C.baileyi and C.galli. Also results showed a significant difference to study's months in infection , the highest ratio of infection was in Spring and then in Autumn , Winter and the  lower ratio was in Summer with infection ratio 88.4% ,64.1%,56.1% and 32.97% respectively.   Also results revealed that the severity of infection with Intestinal type was between heavy and light infection. Quail birds showed a significant difference in severity infection compared with other birds, it was higher in quail which reached 60.9% and lower in common duck(30.0%) and there was no heavy infection in feral pigeon. when reading of preparation histological sections from intestine of infected birds, the results found a histological changes that parasite induced it in their hosts which included: hyperplasia in infection's regions, necrosis and destroyed in epithelial cells with infiltration of inflammation cells.